Assistive tools for disability arts: collaborative experiences in working with disabled artists and stakeholders. Issue 2 (20th June 2016) - Creed, Chris
Abstract : Purpose: – The purpose of this paper is to provide a review of the experiences in working collaboratively with physically impaired visual artists and other stakeholders (e.g. disability arts organisations, charities, personal assistants, special needs colleges, assistive technologists, etc.) to explore the potential of digital assistive tools to support and transform practice. Design/methodology/approach: – The authors strategically identified key organisations as project partners including Disability Arts Shropshire, Arts Council England, the British Council, SCOPE, and National Star College (a large special needs college). This multi-disciplinary team worked together to develop relationships with disabled artists and to collaboratively influence the research focus around investigating the current practice of physically impaired artists and the impact of digital technologies on artistic work. Findings: – The collaborations with disabled artists and stakeholders throughout the research process have enriched the project, broadened and deepened research impact, and enabled a firsthand understanding of the issues around using assistive technology for artistic work. Artists and stakeholders have become pro-active collaborators and advocates for the project as opposed to being used only for evaluation purposes. A flexible research approach was crucial in helping to facilitate research studies and enhance impact of the work. Originality/value: – This paper is the first to discuss experiences in working with physically impaired visual artists – including the benefits of a collaborative approach and the considerations that must be made when conducting research in this area. The observations are also relevant to researchers working with disabled participants in other fields.